(untitled) (World Economics and Finance Bulletin, 2026)
This article examines international approaches and practical experiences regarding the development of domestic tourism as a priority area for sustainable socio-economic growth. It analyzes models for stimulating domestic tourism demand currently employed in both developed and developing nations—specifically Japan, France, China, Turkey, and Malaysia. The study investigates various instruments, including government support measures, digital promotion strategies for tourism products, travel subsidies, and initiatives for infrastructure development and the creation of regional tourism routes. Drawing upon these international experiences, the article identifies effective mechanisms that can be adapted to enhance domestic tourism systems in countries with emerging tourism markets.